2019
DOI: 10.1007/s12671-019-01100-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Mental Health Effects of Mindfulness Training: a 4-Year Follow-up Study

Abstract: Objectives. Mindfulness-based stress reduction (MBSR) enhances short-term psychological health in clinical and non-clinical samples, whereas studies examining long-term effects are scarce. This study examined whether the effects of a 7-week MBSR programme on mental health persisted at 2-and 4-year follow up and explored possible mechanisms of effect. Methods. In a two-site randomized controlled trial, 288 medical and psychology students were allocated to an MBSR intervention (n = 144) or a no-treatment control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 74 publications
(75 reference statements)
5
37
0
2
Order By: Relevance
“…Details regarding home mindfulness practice frequency and duration during the four-year follow-up period can be found in Solhaug 2017 [ 40 ]. During the six-year follow-up period, the number of participants in the intervention group who reported to practice formal mindfulness exercises decreased from 112 of 140 (80%), one month after the intervention to 28 of 48 (58%), at six-year follow-up, while it increased in the control group from 35 of 138 (25%) to 21 of 58 (36%) participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details regarding home mindfulness practice frequency and duration during the four-year follow-up period can be found in Solhaug 2017 [ 40 ]. During the six-year follow-up period, the number of participants in the intervention group who reported to practice formal mindfulness exercises decreased from 112 of 140 (80%), one month after the intervention to 28 of 48 (58%), at six-year follow-up, while it increased in the control group from 35 of 138 (25%) to 21 of 58 (36%) participants.…”
Section: Resultsmentioning
confidence: 99%
“…Intervention effects are striking, given the relatively low dose of the intervention (a 15-hour course over seven weeks plus 8 x 1 ½ hour booster sessions over four years), the fact that almost half of the students declined to participate in booster sessions offered once a term, and, the intervention group’s decline in frequency of home mindfulness practice over time in contrast with the control group’s increase in practice. While the number of students that reported practicing mindfulness was higher in the intervention group at all time points, better adherence to practice in the intervention group might have led to more robust results, as frequency of formal mindfulness practice has been shown to predict levels of mental distress in the short term [ 41 ], and dispositional mindfulness in the long term [ 40 ]. Another factor that could have influenced the results was the higher baseline levels of AFC in the dropouts compared to the completers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Analyses of associations between formal practice after the course and follow-up outcomes are scarce and inconsistent. [33][34][35] Very few studies have assessed the frequency and effects of informal mindfulness practice, 33 in part because of the difficulties in measuring it. 36 A recent dose-response analysis found that informal practice was associated with improved positive emotions with no association with negative emotions.…”
Section: Comparison With Existing Evidencementioning
confidence: 99%